The negative association of lower body fat mass with cardiometabolic disease risk factors is partially mediated by adiponectin. Issue 12 (20th October 2022) - Gradidge, Philippe Jean-Luc; Jaff, Nicole G; Norris, Shane A; Toman, Marketa; Crowther, Nigel J
Abstract : Gluteofemoral fat correlates negatively with a number of cardiometabolic disease risk factors, but the mechanisms involved in these relationships are unknown. The aim of this study was to test the hypothesis that gluteofemoral fat attenuates the risk of cardiometabolic disease by increasing blood adiponectin levels. This was a cross-sectional study in which arm, leg, gluteofemoral, abdominal s.c. and visceral fat levels were measured by dual-energy X-ray absorptiometry in 648 African females. Fasting serum adiponectin, lipid, insulin and plasma glucose levels and blood pressure were measured. Relationships between variables were analysed using multivariable linear regression and structural equation modelling. Adiponectin correlated positively (β = 0.45, P  < 0.0001) with gluteofemoral fat in a multivariable regression model that included age, height, and arm, s.c. and visceral fat levels. In further regression models, there was a negative correlation of gluteofemoral fat with fasting glucose (β = −0.28; P  < 0.0001) and triglyceride levels (β = −0.29; P  < 0.0001) and insulin resistance (HOMA; β = −0.26; P  < 0.0001). Structural equation modelling demonstrated that adiponectin mediated 20.7% ( P  < 0.01) of the association of gluteofemoral fat with insulin resistance and 16.1% ( P  < 0.01) of the association with triglyceride levels but only 6.67% ( P  = 0.31) of the association with glucose levels. These results demonstrate that gluteofemoral and leg fat are positively associated with adiponectin levels and that the negative association of lower body fat with insulin resistance and triglyceride levels may partially be mediated by this adipokine. Further studies are required to determine other factors that mediate the effect of lower body fat on cardiometabolic disease risk factors.